Peningkatan Keaktifan Belajar Peserta Didik Kelas Xii Melalui Penerapan Model Kooperatif Tipe Number Head Together (NHT) Dengan Dukungan Media Pembelajaran Berbasis Teknologi: Increasing the Learning Activity of Grade XII Students through the Application of the Number Head Together (NHT) Type Cooperative Model with the Support of Technology-Based Learning Media - Ainayah Naim, Andina (Jurusan Pendidikan Teknik Elektro, 2025)
This research aims to enhance the engagement of 12th-grade students at SMAN 21 Makassar through the implementation of the Number Head Together (NHT) cooperative learning model, supported by technology-based media. The type of research conducted is Classroom Action Research (CAR), which is carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection phases. The subjects of the study were 36 students in the 12th grade. The research instruments included observation, questionnaires, and learning outcome tests, which were then analyzed descriptively and quantitatively. The results of the study indicated a significant increase in student participation, which initially was only 25% at the pre-cycle stage, increased to 42% in Cycle I, and reached 81% in Cycle II. The average student score also improved from 64 in the pre-cycle to 80 in Cycle II, while the percentage of students achieving the Minimum Competency Criteria (KKTP) surged from 25% to 83%. The integration of technology, such as Canva and Quizizz, not only enriched the learning materials but also motivated students to actively engage in group discussions.